Fanatisme penggemar K-pop Indonesia: Identitas fandom, tipe kepribadian, dan pemujaan selebritas pada penggemar K-pop - Handoko, Felicia Angela; Rahaju, Soerjantini; Siaputra, Ide Bagus (Konsorsium Psikologi Ilmiah Nusantara, 2024)
The popularity of K-pop in Indonesia is steadily growing each year, highlighting the importance of studies to explore psychological dynamics. This study focuses on investigating the role of fandom identity (fan community identity) and personality according to the Big Five model in relation to celebrity worship among Indonesia K-pop fans. The research participants consisted of 716 K-pop enthusiasts in Indonesia (Mage =20.78; SDage =1.57) selected through purposive sampling. Participants completed the Celebrity Attitude Scale, BFI-2 Short Version, and Fandom Identity Scale. The result did not meet the assumptions for regression analysis, thus Spearman correlation tests were conducted for analysis. The results indicate a significant relationship between fandom identity and celebrity worship, with only the neuroticism personality found to have a low correlation with celebrity worship. The study suggests that fandom identity is more associated with celebrity worship behavior than personality traits, therefore fanaticism is more linked to group actions than individual tendencies.